The Relationship Between Social Attitudes and Responsibilities Towards Geography Learning Outcomes - Yanti, Icha Hilda; Aziz, Daska; Ruliani (Journal Learning Geography, 2023)
The formulation of the problem in this study is whether there is a relationship between social attitudes and responsibility towards the results  of studying geography in Class XI SMA Negeri 5 Banda Aceh. In particular, this study aims to determine whether there is a relationship between social attitudes and responsibility towards the results of studying geography in class XI students of SMA Negeri 5 Banda Aceh. This study uses a quantitative approach to the type of correlation research. The population in this study were geography students of Class XI at SMA Negeri 5 Banda Aceh, which consisted of 67 students. Data collection techniques are documentation and questionnaires. The data analysis technique used is multiple regression test and Spearman Rank correlation test. The relationship between social attitudes and learning outcomes is equal to 0.02. The relationship between responsibility and learning outcomes is -0.14. Based on the value of the relationship, social attitudes and responsibility with learning outcomes have a very weak relationship. Based on the results of processing and discussion, it can be concluded that there is no significant relationship between social attitudes and responsibility for geography learning outcomes for Class XI SMA Negeri 5 Banda Aceh.